PENYELESAIAN SENGKETA TAPAL BATAS ANTARA DESA SINAR HADING DAN DESA RIANGKOTEK DI KECAMATAN LEWOLEMA KABUPATEN FLORES TIMUR - Kolin, Philipus Pandai; Stefanus, Kotan Y; Meyners, David Y (Petitum Law Journal, 2024)
Blureed village boundaries can have a wider negative impact then just the potential for conflict between village because of the strategic and economic potential of a part of the region, such us the impact on social life and government administration and can event havepolitical impact,especially in border village. As happened in Lewolema District, Regency East Flores, there are still two village experiencing conflict regarding their village boundaries each. The method used in research is a descriptive method,namely: legal research that describes or depicts in detail the events or phenomena that occur at the research site. Futhermore, by using a qualitative approach, the aim is to present systematically factual and accurate data regarding the facts in the field that occurred in Lewolema District, East Flores Regency.The result of this research show that: The process of resolving the boundary disput between Sinar Hading village and Riangkotek village in Lewolema District, East Flores Regency has not yet reached a common groud because there is no agreement to resolve this boundary dispute. This can be seen from the prolonged debate between several communities from the two village. The effort taken by the East Flores Regency government to resolve this issue is by mediation. However, this effort has not yet reached a mutual agreement because the Riangkotek Village is still adamant and does not agree to the land. used as a boundary between Sinar Hading Village and Riangkotek Village. Factors inhibiting the resolution of boundary disputes in Lewolema District, East Flores Regency are: Human resources, in this case the lack of public understanding in these two village about the importance of the existence of law in conflict. The second inhibiting factor is the legal culture in Sinar Hading Village and Riangkotek Village, in this case the habits of making their own decisions in their resoective villages.